Association between dietary exposure to chemical contaminants and risk of dementia in older persons - Sophie Lefèvre-Arbogast; Pauline Duquenne; Catherine Helmer; Sophie Auriacombe; Véronique Sirot; Cécilia Samieri (Environment International)
Background: Diet is a major route of exposure to potentially neurotoxic chemicals, yet the epidemiological association of diet contaminants with dementia is unknown. We studied the link between dietary exposure to multiple chemicals and dementia risk in older persons, considering interaction with dietary fat content, which may modify the bioavailability and toxicity of (lipophilic) chemicals. Methods: We included 1,288 non-demented participants from the French Three-City cohort who answered a food frequency questionnaire and 24-hour recall at baseline and were followed for incident dementia. Dietary exposure to 167 contaminants was assessed by combining food intakes with food chemical content from the French second Total Diet Study. We assessed the relation of each individual contaminant with dementia risk using multivariable-adjusted Cox models, exploring effect modification by high-fat diet (>35 % energy from fat). Among high-fat diet consumers, we looked for a signature of contaminants associated with dementia using elastic-net penalization and assess their joint effect. Results: Participants were 76 years-old on average at baseline and 62 % were women. In total, 314 individuals developed dementia over a median 10 years. No contaminant was associated with dementia in the whole population. However, having a high-fat diet was a strong effect modifier for 85 contaminants (FDR-corrected p < 0.05 for interactions) in single-chemical analyses, so that higher intakes were significantly associated with higher dementia risk among high-fat consumers only (n = 386). Among them, a multi-chemical approach revealed a signature of 9 contaminants related to dementia, including 4 perfluoroalkyl substances, 2 flame retardants hexabromocyclododecane (HBCDD) congeners, 2 mycotoxins, and nitrites. This selection included two top hits from the single-chemical analyses (α-HBCDD and perfluorooctanesulfonic acid [PFOS]), and was mainly provided by delicatessen meat, seafood and bread/crispbread. Conclusion: In this large population-based study, dietary exposure to several chemicals was associated with higher dementia risk among older persons consuming > 35 % energy from fat in diet.